(untitled) (Global Journal of Management and Business Research, 2020)
The study examined the factors affecting customers repeat patronage in Southwest Nigerian fast-food restaurants Primary data were source through questionnaire administration Six hundred copies of questionnaire were distributed to customers of selected fast-food restaurants using purposive and systematic random sampling techniques Interviews were also conducted with selected front line staff of the restaurants Data collected were analyzed using descriptive statistical methods The results showed that the factors enhancing customers repeat patronage of fast-food restaurants in Southwest Nigeria were food quality restaurant location and convenience of reach as well as a secured environment The study concluded that fast-food restaurant owners should take advantage of these factors for enhanced performance